2001
DOI: 10.1046/j.1529-8817.2001.037002223.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOACCLIMATION IN THE TROPICAL CORALLINE ALGA HYDROLITHON ONKODES (RHODOPHYTA, CORALLINACEAE) FROM A FRENCH POLYNESIAN REEF

Abstract: Pigment concentration, in vivo absorption, and photosynthetic parameters of the coralline alga Hydrolithon onkodes (Heydrich) Penrose and Woelkerling were compared among samples from a lagoon and from a reef crest of Tahiti Island. Four groups of specimens were considered, differing in their natural exposure to PAR. For specimens collected from the lagoon, the tissues from low-light samples had significantly higher pigment concentration, particularly chl a and phycobilins, compared with the highlight exposed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 73 publications
(90 reference statements)
5
45
0
2
Order By: Relevance
“…Payri et al (2001) reported E k values for Hydrolithon onkodes of 110 µmol photons m −2 s −1 for specimens exposed to high light (1600 µmol photons m −2 s −1 ), reduced to 27 µmol photons m −2 s −1 for specimens exposed to lower light levels (< 200 µmol photons m −2 s −1 ). Roberts et al (2002) and Schwarz et al (2005) also reported low values of E k and E c in Arctic and Antarctic crustose corallines living at 15-20 m depth in very dim light conditions.…”
Section: Photosynthesismentioning
confidence: 99%
“…Payri et al (2001) reported E k values for Hydrolithon onkodes of 110 µmol photons m −2 s −1 for specimens exposed to high light (1600 µmol photons m −2 s −1 ), reduced to 27 µmol photons m −2 s −1 for specimens exposed to lower light levels (< 200 µmol photons m −2 s −1 ). Roberts et al (2002) and Schwarz et al (2005) also reported low values of E k and E c in Arctic and Antarctic crustose corallines living at 15-20 m depth in very dim light conditions.…”
Section: Photosynthesismentioning
confidence: 99%
“…In coralline algae, however, the capacity of carbonate skeleton to enhance light absorption and photosynthetic performance remains unknown (see Payri et al, 2001;Burdett et al, 2014). Recently, Vásquez-Elizondo and Enríquez (2016) documented significant differences in the light absorption properties of three coralline species, before and after exposing the experimental organisms to heat-stress.…”
Section: Introductionmentioning
confidence: 99%
“…This broad taxonomic group is present in virtually every coastal ecosystem, from highly illuminated, intertidal regions to extremely light-limited habitats like rock crevices or depths of 250 m (Johansen, 1981;Littler et al, 1985;Payri et al, 2001;Burdett et al, 2014). The ecological significance of coralline algae varies from playing a fundamental role as ecosystem engineers of highly diverse communities (Foster, 2001;Steller et al, 2003) to being the preferred substrate for settlement of invertebrate larvae (Heyward and Negri, 1999;Williams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Hydrolithon onkodes 200-600 mol photon m -2 s -1 (Payri et al, 2001), ( , Corallina mediterranea Jania rubebs) (Hader et al, 1996). , , (canopy) (Johnson, 1984;Johnson and Mann, 1986).…”
Section: 고 찰mentioning
confidence: 99%